The Statesman's Yearbook 2000
1856 p.
Keywords: For the last 136 years, The Statesman's Yearbook has been relied upon to provide accurate and comprehensive information on the current political, economic and social status of every country in the world. The appointment of the new editor - only the seventh in 136 years - brought enhancements to the 1998-99 edition and these are continued in the 2000 edition. Internet usage figures are included. Specially commissioned essays from major political and academic figures supplement country entries in areas of major upheaval and change. A fold out colour section provides a political world map and flags for the 191 countries of the world. The task of monitoring the pattern or flow of world change is never-ending. However, the annual publication of The Statesman's Yearbook gives all the information needed in one easily digestible single volume. It will save hours of research and cross-referencing between different sources. A prestigious and popular book, The Statesman's Yearbook is updated every 12 months. In a world of continual change The Statesman's Yearbook is a necessary annual purchase.